Exploration of Religious Character Education in Pesantren-Based Madrasah Ibtidaiyah - Sigit Priatmoko; Sidqi Aulia Rahman; Syarifah Rahmatul Inayah; Ratna Ekawati; Siti Salina Binti Mustakim (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2025)
Background & objectives: Character education in Islamic schools has become increasingly important in response to rising moral challenges, and pesantren-based madrasahs are often seen as unique environments for instilling religious values. This study explores the implementation of religious character education in a pesantren-based madrasah ibtidaiyah, focusing on MI Al Maarif 02 Singosari, Malang. Method: Using a qualitative case study approach, this research employed semi-structured interviews, participatory observations, and document analysis, with data analyzed thematically following Miles, Huberman, and Saldaña. Informants, including teachers, principals, and students, were selected through purposive sampling based on their involvement in religious character development. The validity of qualitative data using triangulation of sources and methods to ensure data credibility.Results: The study found that the religious character values promoted at MI Almaarif 02 Singosari, Malang include honesty (shidq), discipline (istiqamah), social care (ta'awun), environmental responsibility (khalifah fil ardh), and love of worship (mahabbah lil ibadah). These values are instilled through a combination of curricular integration, routine religious practices, and community engagement programs. Contribution of theory: The study contributes to Islamic education theory by supporting Lickona’s framework of character development and Al-Attas’s concept of adab, highlighting the importance of integrating both social and spiritual dimensions in character education. Limitations & Recommendations: The research also acknowledges the limitations of its scope, as the findings are based on a single madrasah, suggesting the need for further studies to explore diverse educational settings.